2013
DOI: 10.1111/ijfs.12301
|View full text |Cite
|
Sign up to set email alerts
|

Colour of hot paprika from the La Vera and Murcia regions packaged in different atmospheres during storage

Abstract: Summary This study compared the behaviour of hot paprika (Capsicum annuum L.) samples from the district of La Vera and the region of Murcia packaged in five different conditions during storage. The following five different packaging conditions were used in this study: modified atmosphere packaging with three different conditions (100% N2; 50% N2 and 50% CO2; and 100% CO2), vacuum packaging and traditional packaging (product packaging system without modifying the atmosphere). After the samples were packaged, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Tese were similar to previous studies. Ordonez-Santos et al [18] found paprika packed in CO 2 and under vacuum had higher capsanthin concentrations and ASTA values in both types of samples. Te whole chili in vacuum-packed bags had higher ASTA values compared with jute bags, and the loss of color was relatively higher in vacuum-packed bags under light exposure [17].…”
Section: Color Traitsmentioning
confidence: 93%
See 3 more Smart Citations
“…Tese were similar to previous studies. Ordonez-Santos et al [18] found paprika packed in CO 2 and under vacuum had higher capsanthin concentrations and ASTA values in both types of samples. Te whole chili in vacuum-packed bags had higher ASTA values compared with jute bags, and the loss of color was relatively higher in vacuum-packed bags under light exposure [17].…”
Section: Color Traitsmentioning
confidence: 93%
“…Te content of capsanthin and ASTA values are critical indexes to evaluate the color and storage quality of chili peppers [34][35][36]. However, a gradual discoloration [24], signifcantly decreases in a * , ASTA values and capsanthin content [18,20,24] were observed in all paprika samples during storage. Similar to the previous studies, this study found a general increase in L * and b * , while a * , capsanthin content, and ASTA values decreased with storage time in all groups (Figures 1 and 2).…”
Section: Color Traitsmentioning
confidence: 95%
See 2 more Smart Citations